Financial constraints and the impact of corruption on employment growth. (15th December 2021) - Amin, Mohammad; Soh, Yew Chong
Abstract: Corruption can impose a significant financial burden on firms. Such burden is magnified when firms are financially constrained. The paper applies this idea to the impact of corruption on employment growth. Using firm‐level survey data for 85 countries, we find that corruption hurts more when firms are financially constrained than when they are not. Baseline estimate suggests that a one percentage point increase in overall corruption lowers growth rate of employment by 0.45 percentage points for financially constrained firms but only by 0.08 percentage points for financially unconstrained firms. The result passes several robustness checks.